Meaning and Actualization of Jihad For Students in State Life - Yalizar Rahayu Sitorus; Junaidi Indrawadi; Isnarmi Moeis; Wirdati Wirdati (Fakultas Tarbiyah Institut Agama Islam Sunan Giri Ponorogo, 2023)
This research is attracted by issues where there are various views on the broad meaning of jihad in a multicultural society and the emergence of extremist groups in interpreting and actualizing jihad as a result of these different views. The study aims to analyze the meaning actualization of jihad in the State's life according to STAI As-Sunnah Deli Serdang students, North Sumatra. This research is qualitative with a case study approach. They conducted at As-Sunnah Islamic High School Deli Serdang, North Sumatra. Observation, interviews, and documentation carry out data collection techniques. At the same time, data analysis is done by data reduction, data presentation, conclusion, and verification. The results of the research show that regarding the law of jihad, students agree that the law of jihad is "Fardu Kifayah", namely an obligation that if a group of Muslims has carried it out, then the obligations of other Muslims fall. Even so, under certain conditions, the law of jihad can become "Fardu "'Ain", an obligation for every Muslim. These conditions are when the enemy has attacked when meeting the enemy and when ordered by the legitimate leadership of the State. Student jihad in the State's life can be carried out in all areas, for example, ideology, politics, economy, socio-culture, and defense and security